KONTRAK BELAJAR MELALUI HIDDEN CURRICULUM SEBAGAI BAGIAN DARI PENDIDIKAN KARAKTER SISWA MADRASAH ALIYAH - Maqbulin, Arjunina (Inovasi: Jurnal Diklat Keagamaan, 2018)
The degradation of eastern character (Indonesian) make us upset.This paper is trying to find a solution how to educate character ofstudents without reducing learning hours most of which have beenused by teachers to teach their subject. One way to be conductedby teachers to educate students through hidden curriculum( through the curriculum not included in textual ) is by using learningcontract. Learning contract is agreements between students andteachers about the things that deal with learning activities, includingdiscipline, responsibility and honesty. The agreements carried outin early semester to ensure that the learning activities can be donewell within a semester. Therefore, this paper aims to explain howto grow students good character in the classroom through learningcontract. To make contract learning run well, teacher must alwayscontrol the effectivity of contract learning that have been made.Character education that uses learning contract will make studentshave discipline, honest and responsible characters. That is why, inorder to make learning contract can run well, the method that isused by teacher is by doing observation. Therefore, teacher cancontrol whether the agreements are done or not.